Integrated Itsbat Nikah Services for Indonesian Migrant Workers Cross-Border Community Service Program at the Consulate General of the Republic of Indonesia Kuching, Malaysia - Ani Purwati; Gita Ruslita; Aris Yulia; Liza Marina; Siti Chariyah Batubara (International Journal Of Community Service, 2026)
Indonesian Migrant Workers (Pekerja Migran Indonesia-PMI) constitute a vulnerable population that frequently encounters family-law problems, particularly marriages that are religiously valid but not formally registered. From a legal standpoint, marriage registration is mandatory as an instrument to ensure legal certainty and family protection. In practice, however, many PMI marriages abroad remain unregistered due to limited access to legal information, cross-border administrative barriers, institutional fragmentation, and jurisdictional differences. This situation creates legal uncertainty regarding the status of spouses and children, obstructing the fulfillment of civil rights, access to public services, and family-law protections, thus undermining the state’s mandate to protect PMI and their families. This cross-border Community Service Program (Pengabdian kepada Masyarakat-PKM) aims to bridge the gap between legal norms and lived realities through an integrated itsbat nikah (judicial marriage validation) service model implemented in Kuching, Malaysia. The program employs a socio-legal approach using a participatory community-engagement design combined with applied doctrinal legal research. Data were collected through regulatory review, field observation, limited interviews with PMI and stakeholders, and administrative and legal assistance. Qualitative analysis connected the regulatory framework of marriage, civil registration, and migrant-worker protection with legal service delivery and the social impacts experienced by migrant families. The program’s outcomes indicate that an integrated itsbat nikah model enhances legal certainty for PMI families through judicial validation of marriage and the integration of legal documentation into civil registration processes. The program recommends strengthening cross-border integrated legal services and updating technical policies to better address the structural vulnerabilities of PMI as part of broader efforts to expand access to justice.